A methodology for overall consequence assessment in oil and gas pipeline industry. Issue 3 (28th March 2019) - Chen, Xuefeng; Wu, Zongzhi; Chen, Wentao; Kang, Rongxue; Wang, Shu; Sang, Haiquan; Miao, Yongchun
Abstract : Quantitative risk assessment (QRA) has been widely used in the oil and gas pipeline industry. QRA mainly includes four steps, namely, hazard identification, probability calculation, consequence assessment, and risk quantification. Consequence assessment is an integral part of QRA, which aims to quantify the negative impacts when pipeline failure events take place. However, the current consequence assessment methods mainly pay attention to the determination of the influence area around accidents and to simple assimilations of the losses, ignoring the components of these losses. This leads to the deterioration of the quality of the QRA. In this article, a methodology for overall consequence assessment in the oil and gas pipeline industry is proposed. The methodology mainly involves three stages, namely, identification of the accident scenario, the determination of influence area, and the calculation of possible losses. The most important innovation spot is integrating four aspects of release accident loss into a quantitative model, to calculate a quantitative result of the loss value of a release accident. Therefore, this study can overcome the limitations of current QRA methodologies and improve the quality of QRA for oil and gas pipelines. © 2019 American Institute of Chemical Engineers Process Saf Prog, 38: e12050, 2019